Assessment of bone status and bone turnover in pediatric patients with familiar hypomagnesemia with hypercalciuria and nephrocalcinosis - Beata Bieniaś; Anna Wieczorkiewicz-Płaza; Marcin Zaniew; Barbara Pulcer; Maria Szczepańska; Anna Moczulska; Anna Rogowska-Kalisz; Marcin Tkaczyk; Danuta Ostalska-Nowicka; Katarzyna Zachwieja; Jan Zawadzki; Martin Konrad; et al. (Scientific Reports)
Abstract Familiar hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a rare monogenic tubulopathy. Although some of its features are potentially harmful for skeletal homeostasis, this problem has not been systematically evaluated so far. To evaluate bone mineral density (BMD) in correlation with selected mineral parameters and bone turnover markers (BTMs) to determine the risk of bone mass loss in pediatric patients with FHHNC. The study comprised 28 FHHNC patients aged 4–18 years and 33 healthy, sex - and age matched controls. 6 FHHNC patients showed normal kidney function whereas the remaining 22 presented with CKD grade II- III (median eGFR 73 ml/min/1.73m2). In both groups, serum levels of calcium (sCa), phosphate (sP), magnesium (sMg), 25(OH)D3, 1.25 (OH)2D3, parathormone (PTH) and selected BTMs [BAP, OC, PINP, CTX-I, OPG, SCL, FGF23 and soluble Klotho protein (sKL)] as well as 24-hour urinary calcium excretion (24 h-uCa) were assessed. In addition, BMD of the lumbar spine by DXA method was evaluated. 3 (10.7%) of FHHNC patients showed low BMD (Z-score < -2). Although median Z-score was lower in FHHNC group in comparison to controls, the difference was not significant. FHHNC patients had significantly higher median PTH, 1.25(OH)2D3 and 24 h-uCa values as well as lower sMg. Of the BTMs, they had significantly higher FGF23 and CTX-I levels. CTX-I correlated positively with PTH, FGF23 and SCL but negatively with sMg. Moreover, FGF23 and PTH correlated negatively with sKL. Negative correlation between PTH and sMg was noticed. No significant correlations between measured BTMs and eGFR, sCa, sP, 25(OH)D3, 1.25 (OH)2D3 as well as 24 h uCa were found. None of BTMs significantly correlated with BMD. The results show that pediatric FHHNC patients, regardless of CKD may be at risk for increased bone resorption. Although its pathomechanism is complex, the trigger seems to be Mg depletion, aggravating secondary hyperparathyroidism and leading to the activation of osteolytic processes. However, their clinical significance is unknown, since only minority of patients show osteopenia. Therefore, follow-up of BMD and bone- related laboratory parameters including CTX-I seem to be essential in patients’ monitoring, especially in adults with FHHNC.